2019
DOI: 10.3390/nu11051162
|View full text |Cite
|
Sign up to set email alerts
|

Rice Hull Extract (RHE) Suppresses Adiposity in High-Fat Diet-Induced Obese Mice and Inhibits Differentiation of 3T3-L1 Preadipocytes

Abstract: Obesity is one of major health challenges in the industrial world. Although rice hull has been reported to show various bioactivities, no studies have evaluated its anti-obesity effect. We hope to demonstrate the anti-obesity effect of rice hull extract (RHE) and the underlying mechanism in high-fat diet (HFD)-induced obese mice and 3T3-L1 preadipocytes. Serum lipid profiles were determined by enzymatic methods. Histological analysis of liver and epididymis fat tissues was carried out with hematoxylin and eosi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 43 publications
0
13
0
Order By: Relevance
“…In humans, the reduction of whole-body fat mass after an exercise intervention was associated with increased insulin sensitivity index [ 50 ]. Recently, an extract from rice hulls decreased fat mass by suppressing adipogenic genes in epididymal WAT and liver while enhancing AMPKα protein, consistent with increased fatty acid oxidation [ 51 ]. However, neither AMPKα nor PPARγ abundance changed in visceral WAT after IRW treatment.…”
Section: Discussionmentioning
confidence: 99%
“…In humans, the reduction of whole-body fat mass after an exercise intervention was associated with increased insulin sensitivity index [ 50 ]. Recently, an extract from rice hulls decreased fat mass by suppressing adipogenic genes in epididymal WAT and liver while enhancing AMPKα protein, consistent with increased fatty acid oxidation [ 51 ]. However, neither AMPKα nor PPARγ abundance changed in visceral WAT after IRW treatment.…”
Section: Discussionmentioning
confidence: 99%
“…One study demonstrated that Glycyrrhiza uralensis exhibited antiobesity effects and that several substances, including the LQG in licorice extract, were able to induce UCP1 expression in 3T3-L1 adipocytes, indicating a potential role of LQ in adipocyte browning [ 21 ]. LQG is an important constituent of the flavones in Glycyrrhiza uralensis, which has shown biological properties including anti-inflammation, antihyperglycemia, antineurotoxicity, and cytoprotection [ 18 , 19 , 20 , 28 ]. Additionally, LQG was reported as an aglycone form in vivo [ 28 ] and could be detected in the blood samples of mice administrated licorice-root extract [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Licorice candy is popular in Europe, and teas and soups made with licorice are popular in various regions of Asia. It was shown that LQG exhibits multiple activities such as anti-inflammation, anti-hyperglycemia, and anti-neurotoxicity [ 18 , 19 , 20 ]. Studies show that Glycyrrhiza uralensis has antiobesity potential through the induction of adipocyte browning [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…We have changed the "mg/g" to "μmol/g", please see the red marked part in Table 4 and We have added the sentence of "In our study, MBP was obtained by the reaction of BSP solution and MSP solution in a ratio of 10:1 (v/v). Referring to the concentration group experiment performed in adipocytes [31][32][33][34], the following experimental groups were formulated to conduct experiments.". Please see lines 171-173.…”
Section: Accepted Manuscriptmentioning
confidence: 99%